In search of smart public governance: the case of Lithuania - Siugzdiniene, Jurgita; Gaule, Egle; Rauleckas, Rimantas (International Review of Administrative Sciences)
Faced with rapidly changing economic and societal pressures and complex public policy problems, governments must respond proactively to new challenges. It is just one of the characteristics of being smart. This article analyses the recently introduced concept of smart public governance, a concept that requires better conceptualization. This article defines the characteristics and criteria of smart public governance and suggests an instrument for its assessment. Piloting of the methodology at the central government level in Lithuania suggests that the Lithuanian system of public governance cannot yet be considered a smart social system. Some characteristics of smartness are already well expressed, and some positive examples do exist. However, smart public governance is not yet a part of Lithuania$1 (Bs government culture. - Reproduced.s
Keywords: Smart governance